THE EFFECT OF METACOGNITION, SELF-CONCEPT AND LEARNING INDEPENDENCE ON THE MATHEMATICAL PROBLEM-SOLVING ABILITY OF GRADE XI IPA STUDENTS OF SMAN 1 GOWA - Istianah, Nur; Sukmawati; Halim, St. Nur Humairah (Jurnal Keguruan dan Ilmu Pendidikan (JKIP), 2023)
This type of research was ex-post facto research. The population in this study were all students of class XI of SMAN 1 Gowa while the sample in this study were XI IPA 5 and XI IPA 6, totaling 65 students. The sampling technique used cluster random sampling. Data analysis techniques using questionnaires and tests. Data analysis techniques used descriptive statistical analysis and inferential statistical analysis techniques. The results of this study indicate that (1) Partially, the metacognition variable significantly influences the problem solving mathematics of students of class XI IPA SMAN 1 Gowa of 81.2%. (2) Partially self-concept variables significantly influence the problem solving mathematics of students of class XI IPA SMAN 1 Gowa of 89.6%. (3) Partially the learning independence variable has a significant effect on the problem solving mathematics of students of class XI IPA SMAN 1 Gowa of 74.4%. (4) Simultaneously the variables of metacognition, self-concept and learning independence significantly influence problem solving mathematics of students of class XI IPA SMAN 1 Gowa with a coefficient of determination R2 = 0.924 which means that the metacognition, self-concept and learning independence gave an effect of 92.4% on the problem solving mathematics of students of class